Perbedaan Media Fermentasi Terhadap Produksi Protein Sel Tunggal (PST) Menggunakan Kultur Saccharomyces cerevisiae - Rahayu, Yayuk Putri; Nasution , Haris Munandar; Prasetyo , Healthy Aldriany (Journal of Pharmaceutical and Sciences, 2025)
Utilization of pineapple peel waste and tofu liquid waste can reduce environmental impacts and is an alternative fermentation medium containing cheap and easily obtained carbohydrate sources and has the potential for the growth of Saccharomyces cerevisiae. Single Cell Protein (SCP) is a protein derived from microbes such as yeast. The purpose of this study was to determine the differences between pineapple peel waste and tofu liquid waste with the addition of different nutrients to SCP production using S. cervisiae. The research method was experimental. The independent variables were fermentation medium MK1 (pineapple peel waste; KH2PO4; sugar); MK2 (pineapple peel waste; KH2PO4; (NH4)2SO4; sugar), MT1 (tofu liquid waste; KH2PO4; sugar); and MT2 (tofu liquid waste; KH2PO4; (NH4)2SO4; sugar). The fermentation period was 0, 2, 4, and 6 days. The dependent variables were protein content, cell dry weight, glucose content, pH and temperature. The results of the SCP production research obtained the highest percentage increase in protein content in MT2 media (tofu liquid waste; KH2PO4; (NH4)2SO4; sugar) was 33.33% (day-2, increase in dry cell weight 84.90%), followed by MK2 media (pineapple peel waste; KH2PO4; (NH4)2SO4; sugar) was 13.15% (day-4, increase in dry cell weight 2.77%). The conclusion is that from both pineapple peel waste and tofu liquid waste substrates, the best PST production was obtained with the highest protein content in MT2 (tofu liquid waste media with the addition of KH2PO4; (NH4)2SO4; and sugar).